A Study of Direct Cost Drivers in the Construction Industry in Nigeria - Anthony Okwogume Ujene (Journal of Architecture, Planning and Construction Management, 2020)
Reports of project cost failure have caused the public to lose confidence in the ability of cost advisers to effectively predict and manage construction costs. This study therefore aims at providing a basis for accurate anticipation, allocation and control of direct costs of buildings. The objectives of the study are to evaluate the perceptions of consultants and contractors concerning the factors that drive the escalation and disparities of the direct costs of building and evaluate the level of agreement in their perceptions of effect of the factors among the states in south-south, Nigeria. A pilot study was used to establish population frame, from which 335 consultants and 544 contractors were used for analyses. Data were obtained using structured questionnaire. The tools used for data analysis were descriptive statistics, mean score, Kruskal-Walis test and Mann-Whitney U test. The results show high agreement in contractors and consultants’ perceptions of the relative effect of 80 selected factors among all the states. It is concluded that direct costs are most significantly affected by 13 factors, while the influence of the factors are similar across the states.The study recommends that construction stakeholders should be mindful of the influence of these internal and external factors which cause cost escalation, variation and disparities over places and time during cost anticipation. The factors should be incorporated during cost allocation and utilized during cost control. Adequate priority should be given to effective planning, site and macroeconomic related issues prior to and during construction.